The pore size of chitosan-Aloe vera scaffold and its effect on VEGF expressions and woven alveolar bone healing of tooth extraction of Cavia cobaya - S. Sularsih (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Pore size of scaffolds affects cellular activity, stimulates angiogenetic factors of vascular endothelial growth factor (VEGF), synthesises new blood vessels to regulate migration and proliferation, and accelerates alveolar bone healing of tooth extraction. Purpose: This study aims to analyse the pore size of chitosan-Aloe vera scaffold and its effects on VEGF expression and woven alveolar bone healing of tooth extraction of Cavia cobaya. Methods: 36 male Cavia cobaya, aged 3-3.5 months were divided into six groups: negative control groups (without scaffold), positive control groups (chitosan scaffold), and treatment groups (chitosan-Aloe vera scaffold) on 7- and 14-day observations. Histopathological examination was performed to account the woven alveolar bone areas, and immunohistochemical examination was conducted to examine VEGF expressions on endothelial cells. Data was analysed using a one-way analysis of variance (ANOVA) and least significant difference (LSD) test (p<0.05). Scaffold pore size examination was performed with scanning electron microscope (SEM) with 250x and 500x magnification. Results: Chitosan-Aloe vera scaffold was found to have open pore interconnectivity, the largest pore size was 138.9 μm, while the smallest was 110.5 μm and average pore size was 134.85 μm. The highest expression of VEGF was observed in the treatment group on days 7 (11.5 ±1.39)  and 14 (15.28±1.78), while the largest woven alveolar bone was observed in the treatment group on days 7(17.83±1.47) and 14 (37.67±3.65). Statistically, there was a significant difference between control groups and the treatment groups (p=0.000; p<0.05). Conclusion: Chitosan-Aloe vera scaffold has pore characteristics increasing VEGF expressions and woven alveolar bone areas.